Analysis of the Relationship Between Entrepreneurship Strengthening and Regional Resilience in North Labuhanbatu Regency - Yusri, Mohd. (Economic: Journal Economic and Business, 2025)
This study aims to examine the relationship between strengthening entrepreneurship and regional resilience in North Labuhanbatu Regency. Entrepreneurship is considered a key element in strengthening regional resilience, both in terms of economy, social, and sustainable development. The research approach used is quantitative, with data collection carried out by distributing questionnaires to micro, small, and medium enterprises (MSMEs) and related institutions. The collected data were analyzed using correlational statistical techniques to measure the level of relationship between the variables studied. The results of the analysis show a positive and significant relationship between strengthening entrepreneurship and regional resilience. Increasing entrepreneurial capacity, easy access to capital, innovation in business, and support from local government policies are identified as the main factors in strengthening regional socio-economic resilience. These findings confirm that developing local entrepreneurship can be an effective strategy in building regions that are more resilient in facing various global and national challenges. This study also recommends the importance of collaboration between local governments, the private sector, and the community in strengthening the entrepreneurial ecosystem.